Myanmar Household Welfare Survey Round Four: Note on Sample Characteristics and Weighting - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
The fourth round of the MHWS was carried out between October 12, 2022, and December 30, 2022. In the fourth round, 12,924 households responded to the survey. Of those households, 4831 households were interviewed in the first, second, third and fourth round. . Another 1,924 households were interviewed in Round 2, Round 3 and Round 4 only. Some 127 households rejoined the sample after being interviewed in Round 1 and Round 3. Finally, 3,724 households were added in Round 4 to replace the 2,928 households that dropped out of the sample after the third round. To replace the households that dropped out of the survey, the survey team called 6,641 new households. The households were selected randomly from the phone database, in the same townships as the attrition households, and retained if they had similar characteristics to the attrition households in terms of urban/rural, gender, farm and low education. If the survey team could not meet those criteria, they called households with similar characteristics from the same state/region. As many as 56 percent of new households called responded to the survey in Round 4, compared to only 31 percent of new households in Round 3. A big issue among both old and new respondents continues to be non-response, such as phones were not answered, powered off, or out-of-service, 39.5 percent of calls. For previous respondents, 36 percent of them did not respond to their phones, for any of those reasons, hence the high degree of attrition. Meanwhile, the refusal rate of new households remained low at 3 percent in Round 4 compared to 6 percent in Round 3. It is likely that phone connection and power outages were the main reason that phones were not answered- they were not on. Blackouts not only prevented many households from charging their phones, but also interrupted interviews, if the power was cut-off during the call.